Enhancing zakat compliance through good governance: A conceptual framework - Abdulsalam Ahmed Sawmar; Omar Mohammed Mustafa (ISRA International Journal of Islamic Finance, 2021)
Purpose This paper aims to construct a conceptual framework which explains the relationship between governance of zakat institutions and zakat payment compliance by using the organisational legitimacy theory. Design/methodology/approach This paper adopts content analysis and a review of multidisciplinary literature that primarily relate to zakat institutions, public governance and compliance behaviour. Findings The paper has developed a model, adapted from Abioye et al. (2013), concerning the influence of governance mechanisms on zakat payers' compliance using trust as a moderator. The model comprises four governance mechanisms which influence zakat payment compliance. The four mechanisms include the board and leadership attributes, transparency and disclosure practices, stakeholder management practices and procedural justice. Trust has a moderating effect on the relationship between governance and zakat compliance. Research limitations/implications This model is applicable to regulated zakat systems, where the state has established zakat institutions and regulations for the collection and distribution of zakat, such as Saudi Arabia, Pakistan, Sudan and Malaysia. Originality/value This paper proposes a model, based on Abioye et al. (2013), to explain the influence of governance on zakat payment compliance. The novelty of the study is the addition of one new critical variable, procedural justice, to the Abioye et al.'s (2013) framework. Secondly, the model is proposed for regulated zakat jurisdictions. – – Purpose - This paper aims to construct a conceptual framework which explains the relationship between governance of zakat institutions and zakat payment compliance by using the organisational legitimacy theory. Design/methodology/approach - This paper adopts content analysis and a review of multidisciplinary literature that primarily relate to zakat institutions, public governance and compliance behaviour. Findings - The paper has developed a model, adapted from Abioye et al. (2013), concerning the influence of governance mechanisms on zakat payers' compliance using trust as a moderator. The model comprises four governance mechanisms which influence zakat payment compliance. The four mechanisms include the board and leadership attributes, transparency and disclosure practices, stakeholder management practices and procedural justice. Trust has a moderating effect on the relationship between governance and zakat compliance. Research limitations/implications - This model is applicable to regulated zakat systems, where the state has established zakat institutions and regulations for the collection and distribution of zakat, such as Saudi Arabia, Pakistan, Sudan and Malaysia. Originality/value - This paper proposes a model, based on Abioye et al. (2013), to explain the influence of governance on zakat payment compliance. The novelty of the study is the addition of one new critical variable, procedural justice, to the Abioye et al.'s (2013) framework. Secondly, the model is proposed for regulated zakat jurisdictions.
Keywords: 330; Compliance model; Governance; Trust; Zakat compliance; Zakat institution